The Effectiveness of Play Therapy on Social and Cognitive Skills of Students with Motor Sensory Disabilities - Shirvani, Zahra; Moazami Goudarzi, Soheil; Abyar, Zolfaghar (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2022)
Background and Aim: Game is a part of human life from birth to death. Physiologically, humans need movement and play is an important part of this movement. Humans need to think for their mental and social development, and play is the leaven of thinking. The aim of this study was the effectiveness of play therapy on social and cognitive skills of students with sensory-motor disabilities in Yasuj. To achieve this goal, a statistical population including students with disabilities, motor and sensory motor skills of Yasuj in the academic year 2021 who were studying was used. Methods: The research design is experimental, pre-test post-test with a control group and an experimental group. The sample size is up to 30 students with motor-sensory disabilities (15 in the experimental group and 15 in the control group) using the available sampling method. Experimental group members underwent play therapy during 12 weekly sessions, and advanced perceptual-visual test, Frostig, Godanoff dummy painting test, and Wineland maturity scale were used to collect data. Data analysis was performed at both descriptive and inferential levels. Then, analysis of covariance, t-test and data were analyzed using SPSS-22 software. Results: The results of descriptive statistics and scores of each skill (cognitive, social) in this study showed an improvement in the condition of the experimental group compared to the control group (p≤0.05). Also, the results of analysis of covariance showed that play therapy significantly improved the mean scores of cognitive and social skills in the control group compared to the experimental group (p≤0.05). Conclusion: According to the results, it seems that play therapy can strengthen the social cognitive skills of students with sensory-motor disabilities. Therefore, exceptional pediatricians as well as caregivers are recommended to use play therapy as an intervention method in the treatment of these people.